2023
DOI: 10.3390/atmos14101527
|View full text |Cite
|
Sign up to set email alerts
|

CSES-01 Electron Density Background Characterisation and Preliminary Investigation of Possible Ne Increase before Global Seismicity

Wenqi Chen,
Dedalo Marchetti,
Kaiguang Zhu
et al.

Abstract: In this paper, we provide a characterisation of the ionosphere from April 2018 to September 2022 for 48 investigated months. We used the data of the China Seismo Electromagnetic Satellite (CSES-01), which is a sun-synchronous satellite with five days of revisit time and fixed local time of about 2 a.m. and 2 p.m. The unique orbit of CSES-01 permitted us to produce a monthly background of the ionosphere for night- and daytime with median values acquired during geomagnetic quiet time in equatorial and mid-latitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Several studies proved that Swarm and CSES-01 electromagnetic anomalies statistically preceded several shallow M5.5+ earthquakes [37][38][39][40]. A recent study by Chen et al [41] investigated the relationship between space-time distance and magnitude of the incoming earthquake for the first four years of CSES-01 Ne satellite data. Alterations of the ionosphere before the earthquakes are also commonly investigated using Total Electron Content (TEC), which can be retrieved from different instruments, generally the Ground Global Navigational Satellite System (GNSS) detectors [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies proved that Swarm and CSES-01 electromagnetic anomalies statistically preceded several shallow M5.5+ earthquakes [37][38][39][40]. A recent study by Chen et al [41] investigated the relationship between space-time distance and magnitude of the incoming earthquake for the first four years of CSES-01 Ne satellite data. Alterations of the ionosphere before the earthquakes are also commonly investigated using Total Electron Content (TEC), which can be retrieved from different instruments, generally the Ground Global Navigational Satellite System (GNSS) detectors [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al [13] demonstrated the reliability of in situ plasma parameters derived from the China Seismo-Electromagnetic Satellite. Chen et al [14] showed that CSES-01 Ne data very effectively reflect solar activity, as the trend in the former is highly correlated with the trend of variations in sunspot numbers. Liu et al [15] investigated potential seismic anomalies related to the Luding Ms6.8 earthquake that occurred on 5 September 2022 by analyzing ionospheric, infrared radiation, atmospheric electrostatic field, and hot spring ion data, the results suggested that the observed multi-sphere coupling anomalies were associated with the occurrence of the earthquake.…”
Section: Introductionmentioning
confidence: 99%